(untitled) (Research, Society and Development, 2026)
Neck trauma is a potentially life-threatening condition due to the high concentration of vital structures in a limited anatomical space. The initial approach in the emergency department plays a crucial role in reducing morbidity and mortality, requiring a rapid and systematic evaluation based on evidence. This study aims to review the initial management of cervical trauma, emphasizing the identification of severity signs, risk stratification, and the appropriate use of complementary exams. This is a narrative literature review based on articles indexed in PubMed and SciELO databases, selected according to clinical relevance and recency. The findings highlight the importance of the Advanced Trauma Life Support (ATLS) protocol, the role of “hard signs” as indicators for immediate intervention, and the central role of computed tomography angiography in the evaluation of stable patients. A structured approach improves diagnostic safety and clinical outcomes.